2021
DOI: 10.1097/01.nep.0000000000000809
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Strategies and Tools for Ensuring Safe and Quality Care: A Scoping Review

Abstract: The aim of this scoping review was to map teaching strategies incorporating Quality and Safety Education for Nurses (QSEN) competencies and assessment tools based on the QSEN framework. METHOD The search was conducted through MEDLINE, Embase, Scopus, and Web of Science databases and carried out through the framework developed by Arksey and O'Malley and revised by Levac et al. RESULTS Thirty-one studies were included. Among QSEN competences, patient-centered care, safety, and teamwork and collaboration were mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This gap could be addressed through stronger academic-practice partnerships for bidirectional workforce planning and education, the transition of new graduates to practice, and regulatory updates. While QSEN gained clear support as an educational framework (Marcomini et al, 2021), the small number of articles from practice perspectives indicates a gap in practice implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gap could be addressed through stronger academic-practice partnerships for bidirectional workforce planning and education, the transition of new graduates to practice, and regulatory updates. While QSEN gained clear support as an educational framework (Marcomini et al, 2021), the small number of articles from practice perspectives indicates a gap in practice implementation.…”
Section: Discussionmentioning
confidence: 99%
“…The 2003 IOM Health Professions Education report that inspired the development of QSEN cited education as the bridge for improving quality and safety outcomes by integrating the six essential competencies across health professions education. While QSEN gained clear support as an educational framework (Marcomini et al, 2021), the small number of articles from practice perspectives indicates a gap in practice implementation. Education is a forerunner for practice change, but it may be that the initial focus of QSEN on education limited its adoption in practice settings.…”
Section: Discussionmentioning
confidence: 99%
“…BY AMANDA JENKINSON, PhD, RN, CNE; TERESA WENNER, EDD, MSN, RN-BC, CNE; KAREN WATERFALL, MSN, RN-CCNE; ANITA FENNESSEY, DRNP, RN, CNE; AND MARIANN KERR, PhD, MSN, RN, PCCN-K, CNE N ew graduate nurses require knowledge, skills, and attitudes that will allow them to adapt to an ever-changing healthcare environment where patient safety and quality of care are paramount. 1 Research has demonstrated that new graduate nurses lack critical thinking skills as they transition from students to professional nurses. 2 Nurse educators must adapt their curricula to address the disconnect between the knowledge and skill sets learned in school and the clinical practice expectations of the healthcare setting.…”
Section: Video-recorded Unfolding Case Studies To Improve Clinical Ju...mentioning
confidence: 99%
“…New graduate nurses require knowledge, skills, and attitudes that will allow them to adapt to an ever-changing healthcare environment where patient safety and quality of care are paramount 1. Research has demonstrated that new graduate nurses lack critical thinking skills as they transition from students to professional nurses 2.…”
mentioning
confidence: 99%
“…Emphasis has been placed on nursing programs to develop and implement learning activities that target the different competencies. Some suggested teaching strategies to meet the QSEN competencies include: simulation-based learning, reflective practice (case studies and reflective writing assignments), online modules/digital media assignment, educational workshops, visual art, problem-based learning, and complex education interventions (Marcomini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%